Prediction of Esophageal Varices by Non-Invasive Markers in Patients of Hepatic Cirrhosis due To Chronic Hepatitis C - Hafiza Faiza Rauf, Mahwash Rana, Adeel Ahmad, Khalid Waheed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Esophageal varices develop as a consequence of portal hypertension in patients with chronic liver disease. Predicting the varices by non-invasive methods at the time of registration is likely to predict the need for prophylactic β blockers or endoscopic variceal ligation in patients with cirrhosis and portal hypertension. Objective: To evaluate the accuracy of combined non-invasive parameters in predicting the presence of esophageal varices in patients with hepatic cirrhosis due to chronic hepatitis C, using the positive predictive value (PPV) as a measure of performance. Methods: In this cross-sectional study conducted in the Department of Medicine, Unit-I, Sir Ganga Ram Hospital, Lahore, 125 patients fulfilling the inclusion criteria were included. Platelet count, Prothrombin Time/International Normalized Ratio (PT/INR) and portal vein diameter was assessed. Upper gastrointestinal endoscopy was done in all patients to check the presence or absence of esophageal varices. Results: Mean age of the patients was 52.52±8.39 years with 64% males. Mean PT was 10.09±3.13, mean INR was 1.75±0.22, mean platelet count was 83.56±13.47 while mean portal vein diameter was 13.79±0.84. In 61 patients (48.8%) esophageal varices were present on endoscopy and in 85 patients (68%) esophageal varices were predicted by combined non-invasive parameters. Positive predictive value of combined non-invasive parameters was 71.7%. Practical implications: Noninvasive predictors can be used as a screening tool to decide need for preventive drug therapy in esophageal varices and thus help reduce the workload and financial burden of routine endoscopies in all cirrhosis patients. Conclusion: The results suggest that combined non-invasive parameters may be a useful tool in the prediction of esophageal varices in patients with hepatic cirrhosis Keywords: Esophageal varices, Non-invasive predictors, Portal hypertension